2020
DOI: 10.1111/jre.12739
|View full text |Cite
|
Sign up to set email alerts
|

Molecular inflammation and oxidative stress are shared mechanisms involved in both myocardial infarction and periodontitis

Abstract: Background and Objective: Our aims were to improve the understanding of the pathogenic relationship between cardiovascular diseases and periodontitis and to generate new perspectives in the prevention and treatment of acute myocardial infarction (AMI) and periodontitis. The present study evaluates possible differences in inflammation, oxidative stress, and autophagy markers among subject suffering AMI, periodontitis, or both, to explore possible common pathogenic mechanisms. Material and Methods:A total of 260… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 60 publications
(81 reference statements)
0
33
0
Order By: Relevance
“…Recently, increasing evidence has shown that this condition is also closely associated with excess OS. 26 Excessive accumulation of ROS in periodontal tissues is an important cause of tissue injury during periodontitis. 27 Moreover, OS mediates the relationship between periodontitis and systemic diseases, including cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, increasing evidence has shown that this condition is also closely associated with excess OS. 26 Excessive accumulation of ROS in periodontal tissues is an important cause of tissue injury during periodontitis. 27 Moreover, OS mediates the relationship between periodontitis and systemic diseases, including cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“… 27 Moreover, OS mediates the relationship between periodontitis and systemic diseases, including cardiovascular diseases. 26 , 28 Thus, amelioration of OS damage is important for the treatment of periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Most cardiovascular diseases (CVD) are associated with atherosclerosis, a progressive chronic inflammatory process. Furthermore, inflammation represents the key mechanism of atherosclerosis since plaque progression and instability are triggered and favored by inflammation [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidant therapy is emerging as a promising new paradigm as prophylactic and therapeutic agents [ 13 ]. The reduction of molecular oxygen to hydrogen peroxide is accompanied by a large free energy release that can give rise to free radicals and reactive oxygen species [ 14 ]. They play a crucial role in normal physiological processes like response to growth factors, immune response, and apoptotic elimination of damaged cells.…”
Section: Introductionmentioning
confidence: 99%